What Drives Endorsement Earnings for Superstar Athletes? - Daniel Rascher; Terry Eddy; Giseob Hyun (Journal of Applied Sports Management, 2017)
Athletes’ endorsement earnings receive significant attention in the trade/popular press, but the academic literature on this issue is sparse. Thus, the purpose of the study was to examine factors that drive variation in endorsement earnings. Resulting analyses indicated the Positive Q Score measure (likability) was worth about $750,000–$1 million for each unit of the scale, while the Negative Q Score measure was statistically insignificant. One unit increases in Exposure and Familiarity were worth roughly $600,000 and $200,000, respectively. These findings can be used by athletes, agents, and sponsors to determine estimates, or fair-market value, for endorsement deals.
Keywords: Endorsers; Q score; regression models; sport sponsorship; value